2022
DOI: 10.3390/ijerph19116645
|View full text |Cite
|
Sign up to set email alerts
|

Laccase–TEMPO as an Efficient System for Doxorubicin Removal from Wastewaters

Abstract: A large number of drugs are used to treat different diseases, and thus to improve the quality of life for humans. These represent a real ecological threat, as they end up in soil or ground waters in amounts that can affect the environment. Among these drugs, doxorubicin is a highly cytotoxic compound used as anticancer medicine. Doxorubicin can be efficiently removed from wastewater or polluted water using a simple enzymatic (biocatalytic) system, employing the oxidoreductase enzyme laccase and a stable organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…They have been identified in wastewater near hospitals at concentrations ranging from 0.02 to 0.025 µg/L [7], and their removal in WWTP is not consistently effective [8,[88][89][90]. The effectiveness of laccase was evaluated using doxorubicin and etoposide as model anticancer drugs [83][84][85].…”
Section: Cytostaticsmentioning
confidence: 99%
See 3 more Smart Citations
“…They have been identified in wastewater near hospitals at concentrations ranging from 0.02 to 0.025 µg/L [7], and their removal in WWTP is not consistently effective [8,[88][89][90]. The effectiveness of laccase was evaluated using doxorubicin and etoposide as model anticancer drugs [83][84][85].…”
Section: Cytostaticsmentioning
confidence: 99%
“…Doxorubicin is a widely used anticancer drug for the treatment of various types of cancer. In both studies that dealt with the elimination of this drug from a solution, laccase from T. versicolor (Sigma-Aldrich) was used [83,84]. In both cases, either fluorescence spectrophotometry (λ ex = 480 nm, λ em = 598 nm) [83] or VIS spectrophotometry (λ = 480 nm) [84] was used to determine the residual drug concentration.…”
Section: Cytostaticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Redox mediators are low-molecular-weight compounds that are easily oxidized by laccases and produce reactive radicals that can further oxidize complex organic compounds such as pollutants. In the laccase-mediator system (LMS) for degradation of pollutants, it was reported that 2,2 ′ -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 1-hydrobenzotriazole (HBT), or (2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO) could enhance the oxidation rate of the laccase substrates [62,63]. Although these synthetic mediators are useful for the reactions of organic compounds, there are still challenges in their utilization in industrial processes owing to their high cost, toxicity, and reuse-associated problems.…”
Section: Degradation Of Pollutants Using Enzyme-immobilized Reactorsmentioning
confidence: 99%